Respostas

2014-01-05T14:37:26-02:00
X² - 10x + 8 = - 1
x² - 10x + 8 + 1 = 0
x² - 10x + 9 = 0
a = 1                b = - 10                c = 9
Δ = b² - 4 . a . c
Δ = (- 10)² - 4 . 1 . 9
Δ = 100 - 36
Δ = 64
x = - b ± √Δ 
     ---------------
        2 . a
x = - (- 10) ± √64
     ----------------------
             2 . 1
x = 10 ± 8
     -----------
         2
x' = 10 + 8 
          2
x' = 18 ÷ 2
x' = 9

x" = 10 - 8 
          2
x" = 2 ÷ 2
x" = 1

Resposta: {9; 1}

Conferindo:
x² - 10x + 8 = - 1
9² - 10 * 9 + 8 =
81 - 90 + 8 =
- 9 + 8 = 
- 1

1² - 10 * 1 + 8 =
1 - 10 + 8 =
- 9 + 8 =
- 1
Comentário foi eliminado
De nada!
Comentário foi eliminado
:)